Этно-политические проблемы древней истории Грузии (Мосхи) - Хазарадзе, H. B. (1984)
Chazaradze, N. V.; Ethno-Political Problems of the Ancient History of Georgia (the Moschi); Georg., mit russ. und engl. Résumés; u.a. zu Muški.